Of vessels and cells: the spatial organization of the epididymal immune system. (20th May 2019) - Guiton, R.; Voisin, A.; Henry‐Berger, J.; Saez, F.; Drevet, J. R.
Abstract: Background: One third of infertility cases in couples worldwide has an exclusive male origin and immune disorders, essentially due to repetitive infections, are emerging an cause of male infertility. As the place of sperm maturation, epididymis must be preserved from excessive immune responses that may arise following infections of the male genital tract. At the same time, epididymis must set and maintain a tolerogenic environment in order not to destroy sperm cells that enter the tissue at puberty, long after the immune system has been taught to recognize self pathogens. The immune cells that populate the epididymis have raised growing interest over the last thirty years but they may be not sufficient to understand the immune balance existing in this organ, between immune response to pathogens and tolerance to spermatozoa. Indeed, immune cells are the most motile cells in the organism and need blood and lymphatic vessels to traffic between lymphoid organs and sites of infection to induce efficient responses. Objectives: To review the literature on the blood and lymphatic vessels, and on the immune cells present at steady state in the rodent epididymis (rat and mouse). Materials and methods: PubMed database was searched for studies reporting on the spatial organization of the rodent epididymal vasculature and immune cell types at steady state. This search was combined with recent findings from our team. Results: At steady state, the rodent epididymis presents with dense blood and lymphatic networks, and a large panel of immune cells distributed across the interstitum and epithelium along the organ. Conclusions: The immune system of the rodent epididymis is highly organized. Exploring its functions, especially in an infectious context, is the essential coming step before any transposition to human.